Partisipasi Citizen Journalism Terhadap Media Online Untuk Menambah Jumlah Followers Di Akun Instagram Medan Talk - Indah Ajeng Prilicia (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
Citizen journalism or to journalists residents in indonesia is relatively new citizen journalism can report a lot of things important quickly before conventional media reported a similar story. A medium that most often used citizen journalism that is social media. Medan talk is one of instagram account who became a container work citizen journalism or contribution of the community that is shaped siber media. This study attempts to mendiskripsikan participation of the community towards instagram account medan talk as one of citizen journalism account in medan. This the kind of research quantitative descriptive uses the method, the size of the population 483 and sample 83 people. The withdrawal of technique sample with simple as using random sampling with using analysis single table.  The results of research conducted in variable x by an indicator of how the time it takes to trust the contents of the message to post news medan talk aalah most dominant with the percentage of 30.2 % , in variable y with the indicators happy to talk to be a place for learning lessons be journalists residents most dominant 61.4 from % with the percentage of as much as. Key Word: Citizen journalism , medan talk , participation